Enhancement of Expansive Soil Properties by Water Treatment Sludge Ash in Landfill Liners - Al-Soudany, Kawther Y. H.; Fattah, Mohammed Y.; Rahil, Falah H. (Salehan Institute of Higher Education, 2024)
This study aims to enhance the suitability of expansive clayey soils for use as landfill liners by incorporating water treatment sludge ash (WTSA). Expansive soils, prone to swelling and desiccation cracking, compromise landfill liner integrity, increasing the risk of groundwater contamination. Local soils often do not meet the requirements for hydraulic conductivity and stability, prompting the use of additives like bentonite. However, bentonite-treated soils still face challenges in tropical regions due to moisture loss and cracking. This research investigates the effects of adding WTSA to bentonite-treated soils to mitigate swelling and shrinkage issues. Several geotechnical tests were conducted, including hydraulic conductivity, free swell percentage, swelling pressure, volumetric shrinkage, and desiccation cracking. Results show that WTSA significantly reduces hydraulic conductivity, free swell percentage, and swelling pressure, meeting the standard requirements for liners (hydraulic conductivity of at least 1×10-9m/s and volumetric shrinkage of at least 4%). Moreover, WTSA addition reduces desiccation cracking to acceptable levels, demonstrating its potential as an effective reinforcement material. This study introduces an innovative approach to using WTSA, a waste product, as a sustainable alternative to conventional liner materials, reducing environmental impact and enhancing landfill liner performance. Doi: 10.28991/CEJ-2024-010-11-04 Full Text: PDF